Management Accounting - Two Research Dimensions - Łada , Monika; Kozarkiewicz , Alina (Studia Oeconomica Posnaniensia, 2014)
The aim of this paper is to present and compare the key issues relating to research in the field of management accounting. The discussion focuses on indicating the two dimensions in which the research is conducted. The first dimension relates to theory, the body of knowledge and the practice of management accounting. In the second dimension, the multiplicity of social and economic theories that have been applied to study specific phenomena and practices within management accounting systems are indicated. This demonstration of the variety of research directions leads to the conclusion that both dimensions of research are complementary in explaining the reality; however, from the perspective of an individual researcher they pose different requirements in terms of research goals and methodology.